Influence of religion on healthcare professionals’ beliefs toward teenage sexual practices in Malaysia - Abdul Hamid, Siti Hazariah; Fallon, Debbie; Callery, Peter (UI Scholars Hub, 2020)
Background: Teenagers are influenced by their surroundings, and this may also include their sexual behavior or societal responses to this type of behavior. It is important to understand the complexity of religious mandates and sociocultural disapproval of premarital sex from the perspectives of healthcare professionals. Methods: This qualitative study aimed to explore the influence of religion on healthcare professional’s beliefs toward providing sexual and reproductive health information and treatment. An interview topic guide was used in the in-depth interview of 32 healthcare professionals in several health clinics in Malaysia. The data were transcribed and entered into the NVivo 11 software. Thematic analysis was used to evaluate the data. Results: The findings show that some healthcare professionals positively incorporated Islamic beliefs into sexual health education session but excluded the contraception information. This study also highlights the strategies used by healthcare professionals (discourse on risk, being selective, maintaining their own honor) when providing sexual health services to teenagers. Conclusion: These findings revealed how religion perpetuates a “moral” approach in the provision of sexual health services that potentially affects teenagers’ access to healthcare.